GE_GERICHTE C/318/2014 vom 28. August 2015 - GE Cour de justice (2015)
OBLIGATION D'ENTRETIEN; FRAIS(EN GÉNÉRAL); REVENU HYPOTHÉTIQUE; ACTIVITÉ LUCRATIVE INDÉPENDANTE; CONCUBINAGE; PRÉVOYANCE PROFESSIONNELLE | CC.285; CC.125